Healing trauma in a traumatising environment with young adult men - Laura E. McMinn; Geraldine Akerman; Eileen Gaffney (Journal of Men's Health, 2024)
In this article, the authors outline the interventions offered by the Offender Personality Disorder (OPD) Pathways Complex Needs Service (PCNS) in a Young Offenders Institute and Category C men’s prison for addressing trauma with young adult men within the prison environment and highlight the challenges of trauma-informed practice and interventions within this context. The importance of collaborative work with the young men will be emphasised within the development of clinical formulations and responsive treatment plans. Direct and non-direct trauma therapies offered by the PCNS will be outlined (e.g., Eye Movement Desensitisation and Reprocessing (EMDR) Therapy, sensory approaches). The article will emphasise the importance of adopting a multidisciplinary and system-wide approach to healing trauma, and the crucial role of the PCNS prison officers. The various clinical spaces available for staff to process traumatogenic material will be highlighted as key to maintaining staff wellbeing and resilience. A reflection from a prison officer working in the service will be provided. This article aims to highlight the importance of adopting a holistic and system-wide approach to healing trauma for young men in custody.